HUBUNGAN DURASI PENGGUNAAN GADGET DENGAN KEMAMPUAN MENGINGAT PADA ANAK USIA DINI (4-6 TAHUN) DI TK PGRI SEMPOLAN KECAMATAN SILO KABUPATEN JEMBER: Correlation between Duration of Gadget Use and Memory Ability in Early Childhood (4-6 years) in PGRI Sempolan Kindergarten - Muslikah; Yessy Nur Endah Sary; Dwi Anggun Lestari (Forind Press, 2024)
The ability to remember in early childhood 4-6 years is influenced by various factors, nowadays early childhood is often exposed to gadgets. This study aims to identify the duration of gadget use, identify the ability to remember in early childhood, and analyze the relationship between the duration of gadget use with the ability to remember early childhood aged 4-6 years with the duration of gadget use ≤ 1 hour a day (rarely use gadgets) and the duration of gadget use > 1 hour a day (frequent use of gadgets). This research uses quantitative research with data analysis techniques using a cluster approach. In this study using simple random sampling. The respondents used were parents of early childhood, given a questionnaire containing the relationship of the duration of gadget use to the ability to remember children aged 4-6 years as many as 64 respondents. The instrument in this study used a questionnaire on the use of gadgets that had been tested for validity and reliability. As for the results of research on the use of gadgets in early childhood from 64 respondents, it can be identified that more than 50% of children use gadgets, and experience impaired memory skills by 60%. In early childhood should be controlled and accompanied. Parents can distract from playing gadgets by facilitating physical activity because it can stimulate the child's brain to develop children's skills and intelligence. So it can be concluded that there is a correlation between the use of gadgets with the ability to remember children with a very strong level of relationship.